Saccharomyces boulardii interfere nas vias de sinalização celular NF-kB, MAPK E TLR/MyD88 alteradas pelo 5-fluorouracil - Justino, Priscilla Fernanda Campos (2016)
Introduction: Intestinal mucositis is a frequent side-effect associated to 5-fluorouracil (5-FU) clinical use and results in inflammatory events. It is characterized by epithelial ulcerations in the mucosa and clinical manifestations of abdominal pain, nauseas and diarrhea. Saccharomyces boulardii is a probiotic yeast which has been shown to protect the gastrointestinal microflora from disequilibrium and from associated gastrointestinal disorders. Aim: To evaluate the effect of treatment with SB in the inflammatory response and in cellular signaling pathways (MAPK and NFkB) and Toll-like receptors 2 and 4, and associated adapter protein (MyD88) in the course of experimental intestinal mucositis induced by 5-FU. Methods: Male Swiss mice (25-30g) were treated with 5-FU (450 mg / kg, i.p.) or saline (control). The SB group received for 3 consecutive days only the SB (1,109 CFU / kg, gavage) until the day of sacrifice. 5-FU group received 5-FU+SB for 3 consecutive days after administration of 5-FU. On the 4th day after 5-FU or 5-FU + SB, the animals were sacrificed, samples of jejunum and ileum were removed and the general parameters of mucositis were evaluated (WBC, loss of weight, diarrhea, histology and MPO). It also used the Caco2 cells treated with 5-FU (1mM) and SB for 24h. We also evaluated the inflammation and cellular signaling pathways, for that evaluate the expression of NFkB, IkB, MAPK (p-ERK1 / 2, p38- p, p-JNK), iNOS, inflammatory proinflammatory cytokines (TNF-α, IL-1β, CXCL1, IL-8, IL- 4, IL-6, IL-12, IFN-ɣ), toll-like receptors 2 and 4 and MyD88. Immunohistochemistry and ELISA methods were used for the analysis in animal tissues and used qPCR techniques and WB for cell analysis. Results: Treatment with 5-FU was able to induce intestinal injury with a significant impairment of epithelial barrier function in the presence of the following changes: severe shortening of the villus, crypts of partial necrosis, vacuolization of cells, infiltration and mono polymorphonuclear, increased concentration of pro-inflammatory cytokines (TNF-α, IL-1β, CXCL1, IL-8, IL-4, IL-6, IL-12, IFN-ɣ), increased expression of iNOS, changed c expressions of NF-kB and MAPK (p-ERK1 / 2, p38-p, p-JNK) cellular pathways and changed the toll-like receptors 2 and 4 and MyD88. However, treatment with SB significantly reduced intestinal lesions, recovery of the villi, the crypt depth recovery, decreased neutrophil infiltration and iNOS, reducing the concentration of pro-inflammatory cytokines. Reversed the changes caused by 5-FU in cellular pathways NF-kB and MAPK and expressions of TLR2 and TLR4 receptors and MyD88.